Metacognitive interpersonal group therapy for adolescents with avoidant personality disorder: The case of Sofia. Issue 8 (31st March 2022) - Inchausti, Felix; Velázquez‐Basterra, Gala; Fonseca‐Pedrero, Eduardo; MacBeth, Angus; Popolo, Raffaele; Dimaggio, Giancarlo
Abstract: Introduction: Early intervention studies for adolescents and early adults are required to explore the acceptability and effectiveness of psychological therapies across the full range of personality disorders (PDs) beyond just borderline PD. The main aim of the current paper was to describe a Metacognitive Interpersonal Therapy group adaptation for adolescents (MIT‐GA) presenting with PDs featuring overcontrol and social inhibition, and in particular Avoidant PD characteristics. Methods: We report findings from a single case of a female adolescent diagnosed with Avoidant PD providing preliminary data on feasibility and the possible effectiveness of MIT‐GA. Results: Evidence of acceptability and meaningful clinical gains are described. Conclusions: Results suggest that MIT‐GA could be a powerful treatment option in patients with generalized social avoidance who do not currently receive gold‐standard psychotherapeutic treatments. This intervention also appears to be effective and cost‐effective in initiating significant clinical changes in profiles of young patients with non‐borderline PD symptoms.